Antimicrobial biodegradable packaging with nanotechnology application (Research, Society and Development, 2022)
The production of sustainable food packaging from renewable sources represents a prominent alternative to the use of petrochemical-based plastics. For example, starch remains one of the most studied replacement options due to its wide availability, low cost, and significant advances in improving packaging properties. In this context, nanoparticles with antimicrobial properties as additives play a key role in manufacturing renewable active packaging with superior performance. In this review, a comprehensive summary is provided on the research papers that addresses strategies for using active packaging, using starch as a sustainable polymer, and antimicrobial nanoparticles to extend the lifespan of foods. After a brief introduction to the fundamental concepts related to starch and biodegradable and active packaging, details are presented about the latest advances in nanotechnology, which can minimize the impact on the organoleptic properties of food products, as well as an increase in bioactivity, due to the size in nanometric scale to improve the diffusion of active compounds in the matrix of starch-based active film.